(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the frequency of admission hypothermia among VLBW neonates within the first 24 hours of life. Methodology: A descriptive cross-sectional study was conducted from January 2025 to June 2025 after taking ethical approval from institutional ethical review board (124/IRB/SZMC/SZH) and informed consent from parents or guardian at pediatric ward of Sheikh Zayed Medical College/Hospital Rahim Yar Khan. A total of 160 VLBW neonates (<1500g) were enrolled using non-probability consecutive sampling. Hypothermia was defined as an axillary temperature <36.5°C at admission and classified as mild (36.0–36.4°C), moderate (32.0–35.9°C), or severe (<32.0°C). Data on gestational age, birth weight, gender, mode of delivery, and place of birth were collected. Descriptive and inferential statistics were performed using SPSS v20.0, with stratification to identify associations. Results: The frequency of admission hypothermia was 88.8% (142/160). Of these, 50.7% had mild, 38.0% moderate, and 11.3% severe hypothermia. Only 18 (11.2%) neonates were normothermic. All home-born neonates (n=27) were hypothermic (100%) compared to 85.2% of facility-born neonates (p=0.001). No significant association was found with gender, birth weight, or gestational age, although lower gestational age showed a trend toward increased risk. Conclusion: Admission hypothermia is alarmingly common among VLBW neonates, especially those born at home. Strengthening thermal care practices during delivery and immediate postnatal care is crucial to improve neonatal survival.